Tourism-Sensitive Design as a Community Resilience Strategy - Selly Veronica; Afina Nisa Aulia; Inge Gijsbers (Talenta Publisher, 2025)
Jakarta’s urban transformation has brought both opportunity and disruption, particularly for communities affected by eviction and resettlement. Kampung Kunir, once demolished under a flood mitigation policy, has been reimagined through the Kampung Susun Kunir project—a vertical housing initiative that not only restores shelter but repositions the community within the city’s heritage landscape. This study explores how tourism-sensitive architectural design can serve as a strategy for community resilience in post-eviction contexts. Using a qualitative methodology that includes literature analysis, field observation, and in-depth interviews with residents and stakeholders, this research examines four key elements: site placement, attraction-oriented design, social empowerment, and tourism-induced economic opportunities. The findings reveal that strategic design choices have allowed Kampung Susun Kunir to reclaim its cultural identity, foster community pride, and activate new tourism-driven economies. However, full potential remains untapped without integrated tourism pathways and long-term programming. This paper argues that tourism-informed architectural practices—when coupled with community participation—can contribute significantly to urban resilience, cultural continuity, and inclusive redevelopment in heritage-rich cities.